Website-Based Information System for Non-Habitable House Assistance Services in Kayuri Village - Nalu, Sarlin Hona; Talakua, Alfrian Carmen (MALCOM: Indonesian Journal of Machine Learning and Computer Science, 2024)
An uninhabitable house is a house that does not meet the requirements of building safety and minimum adequacy in terms of space and area. In addition, it also pays attention to the quality of construction materials such as walls, roofs, floors to meet the educational aspects for anyone who occupies them. The process of uninhabitable houses is carried out by the Kayuri village government by the village head and in collaboration with the head of the RT / RW / hamlet to collect data on prospective recipients of uninhabitable houses based on the condition of the house such as leaky roofs, coconut leaf walls, dirt floors and too many family members. The problem that often occurs in the process of collecting data on prospective beneficiaries is still in the form of manual methods so that it takes a long time when collecting files and the recipient selection process still conducts meetings between village officials to determine who is and does not deserve to receive uninhabitable housing assistance (RLTH). In writing this research is also in docum.